LINIERISASI KELUARAN PENCATU DAYA MENGGUNAKAN KOMPUTER - Sumariyah, Sumariyah; Endro Suseno, Jatmiko; Arimono, Ibnu (BERKALA FISIKA, 2006)
A power supply with linier output voltage that controlled by computer has been made. The range of output power supply is +2 until +16 volt.             For providing a voltage with a linier output by turning around the potentiometer in the power supply. The potentiometer is turned around by motor stepper that controlled by computer. The step angle of motor stepper is reduced by the gear combination with transmission ratio 59:26. Step angle reduction for mechanical rotate movement are 0.8° per step and with rising of the output power supply 0.1 volt per step.             This system had been realized and can work with voltage that we want and output voltage have a tolerance 0.06